Ke mana harus melangkah?: masyarakat, hutan, dan perumusan kebijakan di Indonesia - Resosudarmo, I.A.P.; Colfer, C.J.P. (Yayasan Obor Indonesia, 2003)
Indonesia contains some of the world's most biodiverse and threatened forests. The challenges result from both long-term management problems and the political, social, and economic turmoil of the past few years. This book explores recent events in Indonesia, while focusing on what can be done differently to counter the destruction due to asset-stripping, corruption, and the absence of government authority. It consists of 16 chapters writen by authors from a wide range of disciplines. It begins with a series of chapters 1-6 that focuses on the links between the government's policies on forests and forest people. The next set of chapters 7-12 turns to in-depth, sector-level analyses of what happened in Indonesia immediately following the president Soeharto's fall. Chapter 13 and 14 focus on Indonesia's experience of the fires in 1997-98. The final chapters 15 and 16 update the reader, focusing on the two most important trends at work in the Outer Islands of Indonesia at this time: decentralization and illegal logging.